KEPEDULIAN SOSIAL: INISIATIF PEMBAGIAN SEMBAKO DAN PAKAIAN LAYAK PAKAI UNTUK KESEJAHTERAAN - Pratolo Saktiawan; Ls. Aurarillysa K. Desviola Psd; Eli Retnowati; Didit Darmawan Darmawan; M. Iqbal Huda (INCIDENTAL : Journal Of Community Service and Empowerment, 2026)
Community service activities through social charity programs, such as the distribution of food packages and wearable clothing, represent a tangible expression of social responsibility aimed at alleviating the burden of underprivileged communities while strengthening social solidarity. This study aims to examine the implementation of these activities in fostering public awareness of charitable giving using the Asset-Based Community Development (ABCD) approach, which emphasizes the identification and optimization of local assets and community potential. The findings indicate that the program provided significant and direct benefits to the recipients, particularly in reducing the economic hardships experienced by vulnerable households. Furthermore, the implementation of the social service program encouraged active community participation, strengthened collaboration among stakeholders, and promoted a sustainable culture of mutual assistance and philanthropy. These results demonstrate that the ABCD approach is effective in enhancing community empowerment while reinforcing social welfare and collective responsibility.